Morphogenetic dispositions for variability in acute kidney injury after cardiac surgery: Pilot study - Karan, Radmila; Kovačević-Kostić, Natasa; Kirćanski, Bratislav; Čumić, Jelena; Terzić, Duško; Milićević, Vladimir; Velinović, Vojislav; Velinović, Miloš; Obrenović-Kirćanski, Biljana (Frontiers in Medicine, 2022)
Background The aim of our study was to evaluate the degree of genetic homozygosity in cardiac surgical patients with postoperative acute kidney injury (AKI), compared to the subgroup without postoperative AKI, as well as to evaluate antropomorpho-genetic variability in cardiac surgical patients with regard to the presence and severity degree of AKI. Materials and methods The prospective cohort study included an analysis of 138 eligible coronary artery disease (CAD) surgical patients that were screened consecutively. The tested group was divided into three subgroups according to RIFLE criteria: Subgroup NoAKI (N = 91), risk (N = 31), and injury (N = 16). All individuals were evaluated for the presence of 19 observable recessive human traits (ORHT) as a marker of chromosomal homozygosity and variability. Results Comparing subgroups NoAKI and risk, four ORHTs were significantly more frequent in the risk subgroup. Comparing subgroups NoAKI and injury, nine ORHTs were significantly more frequent in the injury subgroup; while comparing the injury subgroup and risk, five ORHTs were significantly more frequent in injury than in the risk subgroup. Results also showed a significant increase in the mean value of ORHTs for the injury subgroup compared to NoAKI subgroup (p = 0.039). Variability decreased proportionally to the increase in the severity of AKI (VNoAKI = 32.81%, VRisk = 30.92%, and VInjury = 28.62%). Conclusion Our findings pointed to the higher degree of recessive homozygosity and decreased variability in AKI patients vs. NoAKI individuals, thus presumably facilitating the development and severity degree expression of AKI in patients after cardiac surgery.